Non-intubated Thoracic Surgery: Wedge Resections for Peripheral Pulmonary Nodules - Ambrogi, Vincenzo; Patirelis, Alexandro; Tajè, Riccardo (Frontiers in Surgery, 2022)
The feasibility of pulmonary resections of peripheral lung nodules has been one of the main objectives of non-intubated thoracic surgery. The aim was to obtain histological characterization and extend a radical intended treatment to oncological patients unfit for general anesthesia or anatomic pulmonary resections. Growing evidences are defining the role of wedge resection in early-stage lung cancer treatment especially for frail patients unfit for general anesthesia and anatomic resections with nodules demonstrating a non-aggressive biological behavior. General anesthesia with single lung ventilation has been associated with a higher risk of ventilatory induced barotrauma and volotrauma as well as atelectasis in both the dependent and nondependent lung. Nonetheless, general anesthesia has been shown to impair the host immune system eventually favoring both tumoral relapses and post operative complications. Thus, non-intubated wedge resection seems to definitely balance tolerability with oncological radicality in highly selected patients. Nonetheless, differently from other non-surgical techniques, non-intubated wedge resection allows histological characterization and possible oncological targeted treatment. For these reasons, non-intubated wedge resection is a fundamental skill in the core training of a thoracic surgeon. Main indications, surgical tips and post-operative management strategies are hereafter presented. Non-intubated wedge resection is one of the new frontiers in minimal invasive management of lung cancer patients and may become a standard in the armamentarium of a thoracic surgeon. Appropriate patient selection and VATS expertise are crucial to obtain good results.